(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In this paper, Homotopy analysis method is applied to the nonlinear coupled differential equations of classical Boussinesq system. We have applied Homotopy analysis method (HAM) for the application problems in [1, 2, 3, 4]. We have also plotted Domb-Sykes plot for the region of convergence. We have applied Pade for the HAM series to identify the singularity and reflect it in the graph. The HAM is a analytical technique which is used to solve non-linear problems to generate a convergent series. HAM gives complete freedom to choose the initial approximation of the solution, it is the auxiliary parameter h which gives us a convenient way to guarantee the convergence of homotopy series solution. It seems that more artificial degrees of freedom implies larger possibility to gain better approximations by HAM.